Cover Image, Volume 528, Issue 9. Issue 9 (12th April 2020) - Streeter, Kristi A.; Sunshine, Michael D.; Brant, Jason O.; Sandoval, Aaron G. W.; Maden, Malcolm; Fuller, David D.
Abstract : The cover image is based on the Original Article Molecular and histologic outcomes following spinal cord injury in spiny mice, Acomys cahirinus by David, D Fuller, Aaron Sandoval, Michael Sunshine et al., https://doi.org/10.1002/cne.24836 .